The Challenges in English Academic Writing at The Students of The Faculty of Dakwah at The State Islamic University of Sultan Maulana Hasanuddin Banten - Rosida, Hilda; Istiqomah, Istiqomah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The prevalence of grammatical and punctuation errors is a significant challenge for ESL learners, particularly in their efforts to produce fluent academic English. Students often face challenges when assigned to write scientific papers. They often lack the understanding of the methodologies and protocols required for effective and accurate academic writing. The aim of this study is to investigate the constraints faced in academic writing in the English and to explain the approach used by students to navigate the challenges associated with academic writing in the English. This qualitative investigation examines the difficulties faced by students in academic writing in the English. The data collection techniques in this study are questionnaires and questionnaires. The findings of this study reveal that the main challenges faced by students in academic writing in English include problems related to structure, idea development, and selection of vocabulary related to topics. Strategies used by students to overcome this challenge in academic writing in English consist of learning from examples of academic writing, searching for and reading various references such as journals, books, and papers, and utilizing the